A Intervenção Social com Pessoas em Situação de Sem-Abrigo. O papel das políticas sociais de âmbito nacional e local : https://doi.org/10.53809/TS_ISS_2023_n.4_33-49 ("Temas Sociais" Journal, 2023)
The homelessness phenomenon presents itself as a problem that, even in societies with higher levels of socioeconomic development, has drawn political attention because it constitutes the most serious manifestation of social exclusion, which has provided the design of national and local social policies in recent years.This article results from the reflections of a curricular internship in Social Work and intends to contribute to the systematization of the social policy instruments aimed at homeless people at the national and local levels. For this purpose, the social problem under analysis was conceptualized, political approaches and proposals at the national and local levels were identified, and the intervention of social workers was analyzed considering the main principles, models and instruments and systematized the intervention contexts of Social Work in the city of Porto. Finally, the necessity to deepen the study of this theme is reiterated, using contributions from different disciplinary areas, with a special focus on Social Work, its potentialities and limitations.